EFEKTIFITAS STRATEGI INDONESIA DALAM MENANGANI ILLEGAL FISHING OLEH KAPAL NELAYAN ASING DI KABUPATEN KEPULAUAN ANAMBAS – PROVINSI KEPULAUAN RIAU TAHUN 2011-2014 - Hamdan Dani; Aprizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This reseach is intended to review Indonesia strategyefeectivity in handlingillegal fishing that happen in Anambas Sea. Anambas is a regency which locate inSouth China Sea at the west side of Indonesia. The regency of Anambas Islands isa “fish managing area” (WPP 711) that has estimated fishing arround 1 millionton/year. Strategic position and Anambas potension in the other side has a riskwith illegal fishing activity. Indonesia has tried to handled illegal fishing at thislocation with patrol activity by government institution like TNI-AL, DKPAnambas, Satker PSDKP Anambas and built monitoring post also engagingsociety.Cluasewitz said a strategy as a form of engagements of war objective.Describing this phenomenon with using qualitative method with descriptiveanalysisresearch. Using 2 kind of data, primary and secodary data. Primary datais obstained from interview with witness, informant, and institution, andsecondary data isobstained from library research with document and media.Theory in this research is using strategy theory. Strategi is capability to use poweras instrument and threat. Cluaswitz said a strategy as a form of engagements ofwar objective. To understand effectifity of military strategy with using politicaleffectivity approach and also strategy effectivity. Relevant perspective in thisresearch is realist perspective with security and soivereignity theme. Level ofanalysis is nation-state, state is a dominan a dominant actor in internationalactivity.The result of this research is Indonesia strategy in handling illegal fishing atAnambas sea is not an effective strategy because the monitoring complexity ofillegal fishing at Anambas.Keywords : Effectifity, Strategy, Security, Illegal Fishing and Anambas